Etika Bugis dalam Novel Sajak Rindu Lontara Cinta dari Sidenreng dan Kontribusinya Terhadap Pendidikan Karakter di Sekolah - Dedi Ardiansyah; Munirah Munirah; Andi Agussajim Aj (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to describe the form of Bugis ethics and its contribution to character education in schools in the novel Sajak Rindu Lontara Cinta from Sidenreng. This study used a descriptive method with a qualitative approach. This study used a literary anthropological approach with local wisdom theories. The data were obtained through literature study. Data analysis techniques used data reduction, data presentation, and drawing conclusions. The data of this study were analyzed by describing the forms of Bugis ethics, namely sipakatau, sipakalebbi, and sikapale. The results of the analysis of the novel Sajak Rindu Lontara Cinta dari Sidenreng by S. Gegge Mappangewa found that sipakatau, sipakalebbi, and sikapale contributed to character education in schools as the first step to form good character for students.